The Global Spanish Empire : Five Hundred Years of Place Making and Pluralism - Douglass, John G., 1968-; Beaule, Christine D. (Book collections on Project MUSE., 2020)
"The Global Spanish Empire tackles broad questions about indigenous cultural persistence, pluralism, and place making using a global comparative perspective grounded in the shared experience of Spanish colonialism. Through an expansive range of essays that look at Africa, the Americas, Asia, the Caribbean and the Pacific, this volume brings often-neglected regions into conversation"--